PENGARUH SUSTAINABILITY REPORTING TERHADAP HARGA SAHAM DAN NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 TAHUN 2017 – 2021 DENGAN INTERNAL CONTROL DISCLOSURE SEBAGAI MODERASI - Tiffany, Tiffany; Sjarief, Julianti (ANALISIS, 2023)
This study aims to analyze the effect of sustainability reporting on stock prices and firm value with internal control disclosure as moderation. This study uses secondary data from annual reports and sustainability reporting. The population is a company included in LQ45 from 2017 to 2021. The sample selection used the purposive sampling method in which 22 companies were obtained with a period of 4 years so that 88 data were obtained but there were 15 outlier data so that the observation data only amounted to 73 observation data. Methods of data analysis using path analysis with Process. The program used to process data is SPSS version 25. The results of the study show that sustainability reporting has a positive effect on stock prices and firm value. Internal control disclosure moderates the relationship of sustainability reporting to stock prices and company value. The implication of the research results is that companies need to do  and report sustainability reporting and internal control disclosure properly.